G412(P) Sharing 'best practice' amongst trainees and trainers to optimise the quality of paediatric training. (12th March 2018) - Van de Vijver, M; Prentice, P; Wilkey, O; Kainth, R
Abstract : Aims: The Paediatric Trainee Survey is performed annually in a continuing effort to improve paediatric training across the deanery by anonymously obtaining feedback from all Paediatric trainees about their experiences in training. Every year, this survey highlights a wide variation in quality and practice in training across the deanery. Therefore, this project aims to identify the local practice which makes certain trusts excel in their training feedback and distribute this information across the deanery with the goal of ensuring equal standards and experiences. Method: Using the 2016 Paediatric Trainee Survey, we analysed the quantitative results and identified the top three performing trusts for each of the selected five survey indicators. These indicators covered the following aspects of training; Induction, Internal and external teaching opportunities, management experience and training, clinical leadership training opportunities and teamwork and morale in the department. The College Tutors and Trainee Representatives for the identified trusts were contacted with specific questions related to their indicator to obtain information about their local practice. This information was collated and distributed on the Deanery bulletin and website and at Deanery training days with feedback obtained through discussions with trainees and trainers. Results: Feedback was obtained and analysed from the top performing trusts and common themes in local practices were identified for each of the five survey indicators. These themes were named 'Best Practice' and shared amongst the trainees and trainers in the deanery. Conclusion: This project has highlighted main themes in practices in five key aspects of Paediatric training which have been shared across the deanery to improve the overall standard and experience of Paediatric Training. Subsequent work is required to obtain the same information amongst the remaining survey indicators highlighted in the annual Paediatric Trainee Survey and in distributing these practices to other deaneries in the United Kingdom.